LEARNING ORGANIZATION 2.0: AN EMPIRICAL STUDY OF CONTEXTUAL ADAPTATION IN PT MMI PURWAKARTA - Imam Nurhidayat; Maria Jacinta Arquisola (Faculty of Business, President University, 2022)
Business rapid development with technology advancement urges enterprises to create a sustainable competitive advantage. Being a Learning Organization (LO) becomes favorable, yet cultural backgrounds and the need to adapt with open innovation urge an adapted LO 2.0. This paper aims to study the application in Indonesia’s industrial context, the underlying factors, and obstacles in a manufacturing plant at PT MMI. The preliminary study interview involved four strategic managers, followed by an empirical study surveying the 130 employees using the adapted Learning Organization Questionnaire (LOQ). The analysis used descriptive statistics and a Confirmatory Factor Analysis (CFA). Its findings suggest that PT MMI successfully enhances the practice of LO 2.0 on its contextualized adapted approach such as an innovative environment, effective information sharing, enhancing employee empowerment, supporting employees’ self-development/ mastery, and becoming a facilitative leader with a multi-stakeholder approach. Nevertheless, some factors with marginal mean scores on each dimension risk destabilizing the long-term learning practice in PT MMI, which the leaders should consider improving and strengthening.